PERSONALITY AND ADJUSTMENT TO A LOW-CONTROL SITUATION: THE MEDIATING ROLE OF COPING - Buško, Vesna; Kulenović, Alija (2001)
The hypothesized mediating effects of coping mechanisms in the stress and adjustment processes were tested in a prospective framework with 421 basic military trainees. Structural equation analyses indicated direct relations of personality assessed by NEO-FFI to the changes in psychological adjustment when the model included initial coping measures. Personality effects on adjustment were, however, fully mediated through the measures of later coping.
Projekt MZOS
ENG